Spice Crops Of India - Prem Singh Arya; Prem Singh Arya (Ludhiana Kalyani, 2007)
Idia being "The Home Of spice" and main producer, and exporter in the global Scenario.
Post-harvest Management Diseases of Spice Crops Insect- Pests
Keywords: Post-harvest Management, Diseases of Spice Crops ,Insect- Pests